유리체절제술과 백내장병합수술 시 동시 시행한 후낭절개술 후 앞방 깊이와 굴절력 변화 - 유웅선(Woong-Sun Yoo), 서진석(Jin-Seok Seo), 정지성(Ji-Sung Jeong), 신민호(Min-Ho Shin), 김성재(Seong-Jae Kim), 정인영(In Young Chung) (Daihan angwa haghoi jabji, 2019)
목적: 유리체절제술과 백내장병합수술 시 유리체절단침을 이용하여 후낭절개술을 동시에 시행한 경우 수술 후 앞방 깊이 및 굴절력변화를 확인하고자 하였다. 대상과 방법: 유리체절제술과 백내장병합수술 및 유리체절단침을 이용한 후낭절개술을 받은 20명 20안을 대상으로 하였다. 술 전후의 앞방의 깊이는 샤임플러그 사진기(Pentacam®, OCULUS Optikger te GmbH, Wetzlar, Germany)를 이용하여 측정했으며, 술 후 굴절력은 자동각막굴절측정기를 이용하여 예측한 굴절력과 차이를 비교하였다. 결과: 수술 전 앞방 깊이는 2.58 ± 0.248 mm였으며, 수술 후 1개월째 3.65 ± 0.475 mm로 유의하게 깊어졌으며(p<0.001), 수술 후 3개월째 3.70 ± 0.452 mm로 1개월째와 유의한 차이를 보이지 않았다(p=0.213). 술 전 예측 굴절력은 -0.60 ± 0.809D였고, 수술 후 1개월째 -1.45 ± 1.252D로 술 전 예측 굴절력에 비해 의미 있는 근시성 이동이 관찰되었으며, 이는 3개월째 -1.48 ± 1.235D로 술 후 1개월에 비해 유의한 변화를 보이지는 않았다. 안압상승이나 인공수정체 관련 합병증은 관찰되지 않았다. 결론: 유리체절제술과 백내장병합수술 시 유리체절단침을 이용한 후낭절개술은 술 후 3개월까지 수정체 낭 수축 등으로 인한 인공수정체의 앞방 이동을 방지할 수 있는 유용한 방법이 될 수 있으나 근시화되는 점을 고려하여 인공수정체 도수 계산을 해야할 것으로 생각된다. Purpose: To evaluate the changes in anterior chamber depth (ACD) and refractive error after combined phacovitrectomy with posterior capsulotomy using a vitrectomy probe. Methods: In 20 eyes of 20 patients who underwent combined phacovitrectomy with posterior capsulotomy using a vitrectomy probe, the ACD was measured with Scheimpflug imaging (Pentacam®, OCULUS Optikgeräte GmbH, Wetzlar, Germany) preoperatively and postoperatively. We compared the preoperative desired refraction and postoperative refraction using an autokeratorefractometor. Results: The preoperative ACD was 2.58 ± 0.248 mm; the ACD significantly increased in 1 month postoperatively to 3.65 ± 0.475 mm (p < 0.001), and it was maintained as 3.70 ± 0.452 mm (p = 0.213) at 3 months postoperatively. The preoperative target spherical equivalent was -0.60 ± 0.809 diopters (D). Myopic shifting was noticed at 1 month postoperatively as -1.45 ± 1.252 D, and it changed between 1 month and 3 months postoperatively (-1.48 ± 1.235 D at 3 months postoperatively was not statistically significant). There was no increased intraocular pressure or intraocular lens-related complication. Conclusions: Phacovitrectomy with posterior capsulotomy using a vitrectomy probe might be a useful way to stabilize the axial position of an intraocular lens without constriction of the capsular bag. However, using this procedure, the surgeon must consider the possibility of myopic shifting in the postoperative refractive error. KCI Citation Count: 0